Satisfaction and discontinuation with the use of family planning methods among eligible couples of rural and urban areas of Karimnagar - Gayathry, Dasari; Moluguri, Anil; Gurnule, Sachin; Vallepalli, Chandrasekhar; Guthi, Visweswara Rao (International Journal Of Community Medicine And Public Health, 2019)
Background: Family planning in which the major component is use of contraceptive methods is a key constituent of health services. The growing use of contraception around the world has given couples the ability to have child as they wish and has tremendous life-saving benefits. Therefore, the current study was conducted to assess the family planning practice among the couples of reproductive age group in the field practice areas. Methods: A cross - sectional study was conducted during February 2013-January 2014 among the couples residing in the field practice study areas. A semi-structured questionnaire regarding practices towards family planning was administered to 406 couples of the study area. Results: It has been observed that about, 250 (61.6%) couples were practicing contraception, while 156 (38.4%) were not practicing any method. There was no statistically significant difference observed between the family planning practices of couples in rural and urban area (p=0.54). Conclusions: The study revealed that most of the couples were practicing at least one family planning method with marginal difference in urban and rural area. Among those who were practicing, most common method was tubectomy followed by vasectomy, OCPs and IUDs and most of them were satisfied regarding the adopted method. Sustained efforts on dissemination of information, providing education and increasing communication with couple in reproductive ages and improved family welfare service along with regular availability of contraceptive level would also help in improving adoption and use of family planning measures.